Implementation of Trade Secrets Directive into Lithuanian Law - Birštonas, Ramūnas (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] On 8 June 2016 the directive 2016/943 on the protection of undisclosed know-how and business information (trade secrets) against their unlawful acquisition, use and disclosure was enacted, which should have been implemented by the EU member states into their national laws by 9 June 2018. This would raise important questions how these new rules are compatible with the already existing national laws, what will be the scope of changes and what will be the possible impact on national legal practices. This research paper aims to answer these questions from the perspective of Lithuanian national law. Summary On 8 June 2016 the directive 2016/943 on the protection of undisclosed know-how and business information (trade secrets) against their unlawful acquisition, use and disclosure was enacted, which should have been implemented by the EU member states into their national laws by 9 June 2018. In spite of the certain degree of harmonisation of the trade secrets protection brought by Art. 39 of the TRIPS Agreement the new directive provides for a new set of norms. This would raise important questions how these new rules are compatible with the already existing national laws, what will be the scope of changes and what will be the possible impact on national legal practices. This research paper aims to answer these questions from the perspective of Lithuanian national law. For that purpose the current and newly proposed laws, as well as the Lithuanian case law concerning the protection of trade secrets are analysed and assessed.